Routine Psychological Testing of the Individual Is Not Valid. Issue 4 (August 2019) - Gomes, Cristiano Mauro Assis; de Araujo, Jhonys; do Nascimento, Elizabeth; Jelihovschi, Enio Galinkin
In this article, we present and argue our assertion that current routine psychological testing of individuals is not valid. To support our assertion, we review the concept of ergodicity, Birkhoff's theorem, and Molenaar's manifesto, which together support our contention that the direct transposition of population estimations for producing inferences about the individual is not valid. We argue that this practice of direct transposition is the root cause of why routine psychological testing of individual is not valid. We then provide an example of a common application of psychological testing of an individual, explaining why this practice is not valid. Finally, we discuss how the intraindividual (or within-person) approach provides some prospect for valid individual testing and also introduces new challenges. We hope that our questioning of current psychological testing practices motivates researchers to propose and study novel methodological propositions to address the issues raised by our assertion.